The Role of Digital Transformation, Human Resources, and Marketing on Economic Growth in the Digital Industrial Era: A Bibliometric Analysis in Indonesia Over 1 Decade - Ulumiddin; Donny Melianto; Kurnadi; Siti Mujanah (Outline Journal of Economic Studies, 2025)
This study analyzes the role of digital transformation, human resource (HR) management, and marketing strategies in driving Indonesia’s economic growth in the digital industrial era using a bibliometric approach. Adopting the PRISMA method, 198 indexed articles (2016–2025) were systematically selected. Data were analyzed via VOSviewer to map publication trends, keyword linkages, and key contributors. Results reveal a significant surge in publications (peaking at 50 articles in 2023), with three dominant clusters: (1) synergy between HR and organizational strategy, (2) digital marketing as a catalyst for business transformation, and (3) technological infrastructure as an enabler. Universitas Pamulang and marketing-focused journals emerged as top contributors. The study concludes that digital transformation, HR, and marketing are intrinsically interconnected in accelerating Indonesia’s economic growth, necessitating holistic policy integration for optimal impact.